Questions Frequently Asked of Healthcare Professionals: A 2-Year Data Survey Conducted at a Medical Center. (14th February 2018) - Hou, Chi-Lien; Lu, Ying-Hao; Chien, Shun-Ching; Chen, Hsu-Hui; Chen, Chung-Yu
Abstract : In this descriptive, retrospective study, we analyzed the types of questions posed by healthcare professionals to drug counselors at a medical center and the types of provision of pharmaceutical advice solicited to improve pharmaceutical care quality and establish clear directions for clinical pharmacist training. We collected 8, 558 questions posed by healthcare professionals (physicians, 38%; pharmacists, 39%; nurses, 23%) from the electronic drug information record system from May 2013 to April 2015 in one medical center. Overall, 52% and 45% of calls came from outpatient and inpatient departments, respectively. Telephone was the main route of provision of pharmaceutical advice (total, 6, 035 questions; 72%), and hospital/electronic formulary was the main reference type (43%). The top 10 topics were dosage, alternatives, drug name, usage, adverse drug reactions, medication suggestion, drug compatibility, national health insurance criteria, mechanism, and indications. Pharmacological classification inquiries most frequently addressed antimicrobial agents (20%), and vancomycin was the top single drug. Finally, 67% of calls were completed in 5 minutes. Our results suggest that the systematic organization of issues into a searchable database would reduce inquiry durations and improve work efficiency. Furthermore, the availability of various search tools and methods would quickly provide healthcare professionals with provision of drug information needed to improve patient medication safety.